Borders, Boats and Barges: A UK Post-Election Analysis (Journal of Advanced Research in Social Sciences, 2025)
This paper considers policy and rhetoric surrounding the United Kingdom’s stance on asylum seekers and undocumented migrants. This is considered from a discourse analytic perspective by examining a corpus of data drawn from three sources at critical time points in recent months. One source of data is drawn from the record of a key debate in January 2024 in the House of Commons on the Rwanda Plan Cost and Asylum System. Another data source is the Safety of Rwanda (Asylum and Immigration) Bill itself and explanatory notes, presented in April 2024. The final data source is news media reporting of asylum seekers and undocumented migrants as an issue in the May-through July UK election campaign period and immediately post-election as the new Labour administration took office. The analysis reveals the different political stances taken on the issue of asylum seekers and the ways in which these are bound up with rhetorical constructions of deterrence, human rights, and practicality.